6k+7=43

Simple and best practice solution for 6k+7=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k+7=43 equation:


Simplifying
6k + 7 = 43

Reorder the terms:
7 + 6k = 43

Solving
7 + 6k = 43

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 6k = 43 + -7

Combine like terms: 7 + -7 = 0
0 + 6k = 43 + -7
6k = 43 + -7

Combine like terms: 43 + -7 = 36
6k = 36

Divide each side by '6'.
k = 6

Simplifying
k = 6

See similar equations:

| 2(x+3)=3(2x-10) | | -11x-8+3x=24 | | 2(-7x+6)=-16-7x | | 5.9x=-30.09 | | -5=7+4x | | 2c+3=4(5c-6) | | 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 |

Equations solver categories